The Influence of Motivation, Employee Development and Teamwork on Employee Performance through Employee Engagement in Service Industry Employees - Ameilia Harum Khaerani Taning; Justine Tanuwijaya; Andreas Wahyu Gunawan P (Newinera Publisher, 2024)
Objective: to analyze the influence of motivation, employee development and teamwork on employee performance through employee engagement in service industry employees. Research Method: The type of research method used in this research is descriptive quantitative with a cross sectional design using a questionnaire. The research sample was selected using convenience sampling and snowball sampling methods with a total of 120 respondents consisting of service industry employees in Jakarta and Kalimantan. Data analysis used to test the hypothesis uses Structural Equation Model (SEM) with the software used is SMART-PLS 3 to test direct effects, and SMARTPLS 3.0 Bootstrapping to test indirect effects. Research Results: Motivation, employee development and teamwork have a positive effect on employee engagement. Employee development, teamwork and employee engagement have a positive effect on employee performance. Motivation has a negative effect on employee performance. Employee development has no effect on employee performance through employee engagement. Motivation and teamwork influence employee performance through employee engagement. Managerial Implications: Evaluation material for companies in the service sector that want to improve employee performance by increasing employee motivation, employee development, teamwork and employee engagement.